Her2 expression and gene amplification is rarely detectable in patients with oral squamous cell carcinomas. (20th March 2014) - Hanken, Henning; Gaudin, Robert; Gröbe, Alexander; Fraederich, Meike; Eichhorn, Wolfgang; Smeets, Ralf; Simon, Ronald; Sauter, Guido; Grupp, Katharina; Izbicki, Jacob R.; Sehner, Susanne; Heiland, Max; et al.
<x xml:space="preserve">Abstract</x> Purpose Her2 (ErbB2) transforms cells when overexpressed and is an important therapeutic target in breast cancer. Contrary to breast cancer, studies on Her2 overexpression and gene amplification in squamous cell carcinomas of the head and neck region described largely different results. This study was undertaken to learn more on the prevalence and clinical significance of HER2 amplification and overexpression in squamous cell carcinomas of the head and neck. Materials and methods Her2 expression and gene amplification was analyzed by immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH) on two tissue microarrays composed of 427 squamous cell carcinomas of the head and neck region and 222 oral squamous cell carcinomas. Results were compared with clinicopathological features. Results Her2 expression and gene amplification was rarely detectable in squamous cell carcinomas of the head and neck region and unrelated to tumor phenotype or survival of the patients with oral squamous carcinoma. Discussion Our results demonstrate that Her2 protein and gene amplification was only detectable in a small subset of squamous cell carcinomas of the head and neck region as well as oral squamous cell carcinomas. However, it can be speculated that those few patients with Her2 overexpressing and gene amplificated tumors may possibly benefit from an anti‐Her2 therapy.